Influence of the Purkinje-muscle junction on transmural repolarization heterogeneity. (3rd July 2014) - Walton, Richard D.; Martinez, Marine E.; Bishop, Martin J.; Hocini, Mélèze; Haïssaguerre, Michel; Plank, Gernot; Bernus, Olivier; Vigmond, Edward J.
Abstract: Aims: To elucidate the properties of the PMJ and myocardium underlying these effects. Transmural heterogeneity of action potential duration (APD) is known to play an important role in arrhythmogenesis. Regions of non-uniformities of APD gradients often overlap considerably with the location of Purkinje-muscle junctions (PMJs). We therefore hypothesized that such junctions are novel sources of local endocardial and transmural heterogeneity of repolarization, and that remodelling due to heart failure modulates this response. Methods and results: Spatial gradients of endocardial APD in left ventricular wedge preparations from healthy sheep ( n = 5) were correlated with locations of PMJs identified through Purkinje stimulation under optical mapping. APD prolongation was dependent on proximity of the PMJ to the imaged surface, whereby shallow PMJs significantly modulated local APD when stimulating either Purkinje ( P = 0.0116) or endocardium ( P = 0.0123). In addition, we model a PMJ in 5 × 5× 10 mm transmural tissue wedges using healthy and novel failing human ventricular and Purkinje ionic models. Short distances of the PMJ to cut surfaces (<0.875 mm) revealed that APD maxima were localized to the PMJ in healthy myocardium, whereas APD minima were observed in failing myocardium. Amplitudes and spatial gradients of APD were prominent at functional PMJs and quiescent PMJs. Furthermore, increasing the extent of Purkinje fibre branching or decreasing tissue conductivity augmented local APD prolongation in both failing and non-failing models. Conclusions: The Purkinje network has the potential to influence myocardial AP morphology and rate-dependent behaviour, and furthermore to underlie enhanced transmural APD heterogeneities and spatial gradients of APD in non-failing and failing myocardium.